Analysis of the stick-slip vibration of a new brake pad with double-layer structure in automobile brake system. (1st March 2019) - Wei, Daogao; Song, Junwei; Nan, Yanghai; Zhu, Weiwei
Highlights: A new model of a vibration system with double layer structure is established. The system vibration modes can be changed from period-doubling bifurcation to chaos. The parameters are optimized to improve system stability and shrink chaotic vibration. Abstract: This study establishes a dynamic model of a new brake system with two-layer structure to explore the mechanism of vibration and noise reduction of a brake pad with new structure. The model is used to analyze the effects of parameters of the double-layer pad on the stability and stick-slip vibration characteristics of the brake system. The stability of the brake system is optimized by brake parameters with respect to the stability diagram of brake pressure under a relatively wide range. System vibration modes can be changed from period-doubling bifurcation to chaos based on the variation of brake pressure and the parameters of double-layer pad via numerical analysis. The chaotic vibration region is optimized in this study using the correlation coefficient, which consists of friction-layer pad mass m b2 and connection stiffness k 2 . Results show that the range of chaotic vibration region can be reduced when the friction-layer pad mass and connection stiffness are large.